Model for personnel allocation and selection of off-duty groups in a textile company - Kramer, Hugo Harry F. R.; Subramanian, Anand; DAngelis, Luiz Guilherme Binder; Pires, Carlos Eduardo G. L. (Revista Gestão da Produção Operações e Sistemas, 2008)
This paper deals with the resolution of the personnel assignment problem and the selection of the off-work groups of employees belonging to a certain sector of a major textile industry. This is a problem of great importance for most organizations, since it is fundamental to assign the set of available workers, with distinct levels of skill and qualification, to the best suitable tasks. Hence, a multidimensional assignment model was built, taking into account the operational and functional particularities of the sector, as well as considering the benefit of assigning some worker to a determined section of the same. The optimum solution obtained maximized the global benefit of the assignments and at the same time allowed the identification of the off-work groups of employees in the sector studied. Keywords: Multidimensional assignment problem; Off-work groups; Benefit.